Comparison of EQ-5D and SF-36 in untreated patients with symptoms of intermittent claudication. (1st June 2018) - Vaidya, Anil; Kleinegris, Marie-Claire; Severens, Johan L; Ramaekers, Bram L; ten Cate-Hoek, Arina J; ten Cate, Hugo; Joore, Manuela A
Aim: To compare health-related quality of life (HRQoL) descriptions and utility scores in newly diagnosed peripheral arterial disease (PAD) patients, using two most widely used instruments, EuroQol 5D (EQ-5D) and Medical Outcome Study 36-item Short-Form Health Status Survey (SF-36).Methods: Patients' self-assessment of HRQoL was measured by the Dutch versions of the EQ-5D and SF-36 in the 204 patients.Results: Mean utility scores ranged from 0.675 for Short-Form Six-Dimension, 0.648 for the EQ-5D UK tariff and 0.715 for the Dutch EQ-5D tariff. A moderate correlation between the utility scores was found due to different valuation techniques of these instruments.Conclusion: Both instruments have clinical validity for use in the PAD and can be used alongside each other to provide a holistic assessment of the HRQoL. Before using these two instruments interchangeably for utility score calculations and healthcare resource allocation, a thorough sensitivity analysis is necessary to explore the robustness of the value argument based on these utility scores.